Sosiologi Lingkungan Dalam Lontar Taru Pramana: Manusia, Lingkungan, Dan Pengobatan Tradisional Bali - Adnyana, Putu Eka Sura (Institut Hindu Dharma Negeri Denpasar, 2021)
Lontar Taru Pramana is a lontar containing many types of plants that can be used in traditional medicine. Through the contents of Taru Pramana's lontar text, it is possible to trace the types of plants that have lived and are still growing in Bali's natural ecosystem, of course, with an environmental sociology perspective. The relationship between environmental sociology and Taru Pramana's lontar text semiotics explains the meaning of the relationship between humans and the environment. Three conceptions view nature in environmental sociology, namely: 1) Sustainable use of natural resources; 2)